Syntactically Silent Subjects: Luis Muñoz and the Poetry of Ellipsis - Judith Nantell (Studies in 20th & 21st Century Literature, 2012)
Luis Muñoz (1966) is one of contemporary Spain’s most salient poets. His work has been described as demonstrating a discourse of ellipsis; yet no study has examined in detail his masterful use of syntactic and figurative omission. In fact, even though Muñoz’s published collections to date span two centuries, no single study has been devoted to his decidedly innovative expressivity. His work has been commented on in various panoramic essays considering contemporary poetry published in Spain at this temporal intersection and a number of his poems have been gathered into noteworthy anthologies of this same era. His poetry has been nominated for prestigious awards in Spain and in 2001 Correspondencias ‘Correspondences’ received the fourth Premio Internacional de Poesía del 27 as well as the Premio de Ojo Crítico de Poesía. The present study examines Muñoz’s most recent Querido silencio (2006) ‘Dear Silence’ where ellipsis figures prominently as the poet maximizes and exploits conceptual and linguistic efficiency. In one exemplary poem, “Dejar la poesía” ‘Leave Poetry,’ two syntactically silent subjects engage in an innovative conversation concerning the nature of poetry. At the same time this intriguing dialogue also offers a unique response to the essential question framing this poem and the collection as a whole: Why is poetry an addiction?
Keywords: Luis Muñoz; poetry; ellipsis; silent subjects; syntactic omission; figurative omission